The implementation of enterprise risk management: A study of Malaysian Private Higher Educational Institution / Mariam Setapa and Norhayati Mohmad Zakwan@Zakuan - Setapa, Mariam; Mohmad Zakwan@Zakuan, Norhayati (Unit Penerbitan UiTM Kelantan, 2019)
Enterprise Risk Management (ERM) is fast becoming a key concern in every sector today. Since the 1990s, ERM is a method for managers to identify threats and select the best solution to solve the threats within an organisation. This research paper wishes to develop a conceptual framework of drivers of ERM and the impact of ERM on performance among Private Higher Educational Institutions (PHEIs) in Malaysia. Data were collected from 217 PHEIs listed in the Ministry of Higher Education (MOHE) website through a survey. The respondents were top management of the PHEIs. The data were collected within six months and were analysed using SmartPLS 3.2.1 software. The analysis shows both internal factors (Chief Risk Officer, Top Management, Training and Education), and size and types of institutions were impact of ERM on performance (Management, Financial, Marketing), and external factors (Law and Regulation, Corporate Governance, External Auditor) were not impact of ERM on performance. Thus, hypotheses 1 and 2 were accepted and hypotheses 3 was rejected.